THE IMPORTANCE OF HEALTH LEGAL REGULATIONS ON HOSPITAL B3 WASTE MANAGEMENT - Herman, Putri Widya; Wahyuni, Annisa (Jurnal Informatika Medis, 2023)
The hospital as one of the health service facilities as stated in the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No. 56 of 2015, it is mandatory to carry out B3 waste management which includes reducing and segregating B3 waste, storing B3 waste, transporting B3 waste, processing B3 waste, burying B3 waste, and/or storing B3 waste. Hazardous waste generated from laboratory activities is in the form of residual healing processes for sick people such as additives for washing wounds, blood washing, cancer therapy processes, surgical practices, pharmaceutical products, and residue from incineration processes. The waste generated can pollute the environment. The method used is a systematic review through journal reviews regarding the implementation of legal regulations on the implementation of waste management in hospitals. This systematic review shows that laws and ministerial regulations governing the issue of waste management in hospitals already exist and are clearly described. However, in practice, not all hospitals are aware of managing B3 waste properly. This means that the hospital has not optimally implemented environmental management in accordance with applicable laws and regulations. Lack of concern or commitment from the leadership of hospitals and health care facilities, lack of understanding of health care facility staff, and legal cases in health care facilities. The implementation of laws and regulations related to the management of B3 waste in healthcare facilities, especially hospitals, has generally been carried out based on the applicable legal regulations. However, there are still a number of cases of negligence or lack of awareness on the part of the hospital, both from the low awareness of actors or health workers in providing services so as to make a negative contribution to the environment and society.